2021
DOI: 10.1002/uog.24787
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of possible SARS‐CoV‐2 vertical transmission according to World Health Organization criteria in asymptomatic pregnant women

Abstract: The findings of this study provide evidence of possible vertical transmission of severe acute respiratory sydrome coronavirus 2 (SARS-CoV-2) in asymptomatic pregnant women, using the novel World Health Organizaton criteria for the establishment of mother-to-child transmission of SARS-CoV-2. The presence of SARS-CoV-2 RNA in amniotic fluid and its persistence in the neonate 24 h after birth was demonstrated. What are the clinical implications of this work?This work highlights the importance of testing more than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…This study showed that 53.5% of neonates tested positive for SARS-CoV-2 during the first 12-48 h after delivery, 11% were seropositive and 42% were seronegative. In previous works, we have demonstrated viral presence in fetal tissue (32), in placentas from positive mothers (33,34), and in amniotic fluid and newborns (saliva and rectal swabs) at delivery, even in the presence of maternal IgG (33,34) Our results demonstrate two possible transmission mechanisms. In some cases, we have evidence of (1) maternal infection before birth, (2) in utero exposure (neonatal RT-PCR <24 h), but we do not have evidence of persistence of infection.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…This study showed that 53.5% of neonates tested positive for SARS-CoV-2 during the first 12-48 h after delivery, 11% were seropositive and 42% were seronegative. In previous works, we have demonstrated viral presence in fetal tissue (32), in placentas from positive mothers (33,34), and in amniotic fluid and newborns (saliva and rectal swabs) at delivery, even in the presence of maternal IgG (33,34) Our results demonstrate two possible transmission mechanisms. In some cases, we have evidence of (1) maternal infection before birth, (2) in utero exposure (neonatal RT-PCR <24 h), but we do not have evidence of persistence of infection.…”
Section: Discussionsupporting
confidence: 61%
“…This study showed that 53.5% of neonates tested positive for SARS-CoV-2 during the first 12–48 h after delivery, 11% were seropositive and 42% were seronegative. In previous works, we have demonstrated viral presence in fetal tissue ( 32 ), in placentas from positive mothers ( 33 , 34 ), and in amniotic fluid and newborns (saliva and rectal swabs) at delivery, even in the presence of maternal IgG ( 33 , 34 ). The results shown in the present work do not allow us to conclude about viral transmission, as only one single swab sample was obtained of most neonates.…”
Section: Discussionmentioning
confidence: 95%
“…A prospective, multicenter investigation found that infection occurred in 5.1 % of newborns born to mothers infected with SARS-CoV-2 during pregnancy, implying that SARS-CoV-2 can be transmitted intrauterine [36] . Strong evidence from another study revealed that 12 % of SARS-CoV-2-positive pregnant women transmit the virus intrauterine, and that intrauterine transmission may even occur in asymptomatic individuals [37] . Therefore, SARS-CoV-2 has the potential to affect the auditory system of newborns [6] .…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2 testing in newborns should be emphasized. According to a study, single oral or rectal swabs failed to detect SARS-CoV-2 in 40–60 % of infected infants, whereas dual oral and rectal swabs considerably enhanced the detection rate of SARS-CoV-2 [37] .…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, during this period, the most common cause of maternal death was COVID-19 ( Secretaría de Salud, 2021 ). Although placental COVID-19 infection has been documented in some cases ( Hosier et al, 2020 ; Schwartz and Morotti, 2020 ; Vivanti et al, 2020 ), whether transmission occurs from the mother to the fetus and how the mother-baby dyad is affected during SARS-CoV-2 infection remain controversial issues ( Mirbeyk et al, 2021 ; Salem et al, 2021 ; Sevilla-Montoya et al, 2021 ; Garcia-Flores et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%